Monocyte Adhesion and Plaque Recruitment During Atherosclerosis Development Is Regulated by the Adapter Protein Chat-H/SHEP1. Issue 9 (September 2016) - Herbin, Olivier; Regelmann, Adam G.; Ramkhelawon, Bhama; Weinstein, Erica G.; Moore, Kathryn J.; Alexandropoulos, Konstantina
Abstract : Objective—: The chronic inflammation associated with atherosclerosis is caused by lipid deposition followed by leukocyte recruitment to the arterial wall. We previously showed that the hematopoietic cell–specific adaptor protein Cas- and Hef1-associated signal transducer hematopoietic isoform (Chat-H)/SHEP1 regulated lymphocyte adhesion and migration. In this study, we analyzed the role of Chat-H in atherosclerosis development. Approach and Results—: Using Chat-H–deficient bone marrow transplantation in low-density lipoprotein receptor–deficient mice, we found that Chat-H regulated atherosclerotic plaque formation. Chat-H deficiency in hematopoietic cells associated with lower plaque complexity and fewer leukocytes in the lesions, whereas myeloid-specific deletion of Chat-H was sufficient for conferring atheroprotection. Chat-H deficiency resulted in reduced recruitment of classical Ly6c high and nonclassical Ly6c low monocytes to the plaques, which was accompanied by increased numbers of both monocyte subsets in the blood. This associated with defective adhesion of Chat-H–deficient Ly6c high and Ly6c low monocytes to vascular cell adhesion molecule-1 in vitro and impaired infiltration of fluorescent bead–loaded monocytes to atherosclerotic plaques. In contrast, Chat-H was dispensable for CX3CL1 and CCR1/CCR5-dependent migration of monocytes. Conclusions—: Our findings highlight Chat-H as a key protein that regulates atherosclerosis development by controlling monocyte adhesion and recruitment to the plaques and identify a novel target that may be exploited for treating atherosclerosis. Abstract : Supplemental Digital Content is available in the text.